Analysis of The Indonesian Government Initiative of The National Action Plan on Counter Violent Extremism that Lead to Terrorism - Wulandari, Danny Dwi (Journal of Strategic and Global Studies, 2019)
This article aims to determine the urgency of the government in this case BNPT in initiating the National Plan of Action on counter violent extremism that leads to terrorism. The growing spread of terrorism is evident in the massive nature of violent extremism. Currently the terrorist movement is growing and growing both domestically and at regional or international levels. Indonesia faces an increasingly dynamic and complex development of terrorism in line with changes in the international and regional strategic environment, as well as the changing mode of operation of terrorist attacks. The Collaborative Governance strategy can be used to analyze the urgency of the need for the preparation of the National Action Plan (NAP) where the NAP by BNPT is needed to address push factors and pull factors of terrorist acts in Indonesia. This strategy puts forward involvement together all stakeholders in co-operation and coordination to produce an integrated and comprehensive counterterrorism policy. From the perspective of Collaborative Governance, the establishment of the NAP can be expected to lead to decreased radicalism, increased prevention programs in ministries / institutions, strengthening inter-ministerial / institutional coordination, increasing partnerships between ministries / institutions / institutions civil society, and increased public participation in countering violent extremism leading to terrorism.